Enforcement of Therapeutic Transaction Arrangements as an Instrument of Legal Protection for Patients with Mental Disorders - Anggraeni Endah Kusumaningrum; Siti Farahiyah Ab Rahim; Mahesa Paranadipa Maikel (Lex Scientia Law Review, 2026)
Mental health services face unique challenges because they involve vulnerable patients, requiring strong legal protections. Therapeutic transactions, based on trust, rights, and obligations between patients and health professionals, play a key role in ensuring effective care. However, in Indonesia, challenges remain, including weak implementation of informed consent, limited awareness of patient rights, and inadequate oversight of ethical and legal violations. These issues can lead to malpractice, privacy violations, and inequities in mental health care. This study explores the importance of strengthening Law No. 17 of 2023 as a new and previously unstudied health law that regulates therapeutic transactions to protect the rights of patients with mental disorders. Using a normative legal method, this study analyzes laws, case studies, and academic literature to identify areas for improvement. This study recommends harmonizing regulations with Law No. 17 of 2023 on health, improving informed consent procedures tailored to mental health patients, and enforcing strict sanctions for ethical and legal violations. Additionally, enhancing the capacity of healthcare workers through training, certification, and regular supervision is crucial to maintaining service quality and accountability. Strengthened regulations can create a more fair and transparent relationship between patients and healthcare workers, while also increasing public trust in mental health services. These measures are not only legal protective tools but also steps toward ensuring humane, professional, and fair mental health services. In conclusion, strengthening therapeutic transaction regulations is essential for protecting patient rights, enhancing accountability, and promoting high-quality mental health services that respect human dignity.